Pengaruh Current Ratio, Debt To Equity Ratio, Return On Assets Terhadap Nilai Perusahaan Pada Sektor Pariwisata Tahun 2020 - 2022 - Dianti, Ni Putu Ayu Putri; Yuniasih, Ni Wayan (UNHI Press, 2025)
This study investigates the influence of Current Ratio (CR), Debt to Equity Ratio (DER), and Return On Asset (ROA) on the firm value in the Tourism sector companies listed on the Indonesia Stock Exchange during the period 2020-2022. Using purposive sampling method, the sample consists of 51 financial reports. The research findings indicate that both Current Ratio and Debt to Equity Ratio have a significant positive effect on firm value, while Return On Asset negatively impacts firm value. The significant decrease in Return on Assets (ROA) may be attributed to poor operational performance, such as low sales, declining profit margins, and high operational costs, as well as a decrease in asset utilization efficiency, leading to suboptimal generation of revenue. Overall, these factors can contribute to a reduction in the financial performance of the company.